Effects of an Empowerment Program on Resilience and Posttraumatic Growth Levels of Cancer Survivors: A Randomized Controlled Feasibility Trial. Issue 6 (November 2019) - Üzar-Özçetin, Yeter Sinem; Hiçdurmaz, Duygu
Abstract : Background: Psychosocial empowerment of cancer survivors can help improve their psychological resilience and enhance their posttraumatic growth. However, there is a lack of research exploring the effects of such empowerment programs on resilience and posttraumatic growth of cancer survivors. Objective: The aim of this study was to assess the feasibility of a randomized controlled trial on the effectiveness of an integrated empowerment program on cancer survivors. Methods: We conducted a randomized controlled trial with 89 adult cancer survivors (>25 years old) from 2 oncology hospitals. Using a table of random numbers, they were assigned randomly to the experimental group (n = 45), which participated in 10 sessions of a structured empowerment program, and the control group (n = 44), which received only routine care and no further intervention. Data were collected from patients using the Posttraumatic Growth Inventory and the Resilience Scale for Adults. Results: Posttraumatic growth and resilience levels significantly improved in the intervention group compared with the control group both at the end of and a month after the program. Conclusion: This study's empowerment program is effective in improving posttraumatic growth and resilience levels of cancer survivors who are prone to trauma. Implications for Practice: By enhancing resilience and posttraumatic growth of cancer survivors, the empowerment program may help restore life, and thus its application can contribute to the psychosocial well-being of cancer survivors. Nurses with training and experience can integrate this kind of program into clinical settings.